Effects of Acupotomy on a Dorsal Wrist Ganglion Cyst with Ultrasonography: A Case Report with a 7-Month Follow-up - Jae Hoon Kim; Jung Hee Lee; Cho In Lee; Yun-Kyu Lee; Hyun-Jong Lee; Jae Soo Kim (MEDrang Inc., 2020)
Background This study was conducted to evaluate the clinical effect of acupotomy, a newly upcoming acupuncture treatment method for a dorsal wrist ganglion cyst. Methods A patient with a dorsal wrist ganglion cyst was treated with acupotomy under ultrasonographic guidance. The symptoms caused by the cyst and size of the cyst under ultrasonographic observation were used to evaluate the effect of the acupotomy treatment. Results The numeric rating scale score reduced from 7 to 1.4 throughout the treatment period. The size and swelling of the cyst decreased following acupotomy treatment. Conclusion Acupotomy had a positive clinical effect in the treatment of a dorsal wrist ganglion cyst in this case. Further studies are required for its additional retrospective application